2018
DOI: 10.1111/1556-4029.13774
|View full text |Cite
|
Sign up to set email alerts
|

Homicide in a Horse Barn?

Abstract: As forensic scientists and physicians, forensic pathologists are duty-bound to perform their examinations with integrity and professionalism. The practice of medicine requires knowledge regarding the history and presentation of the patient. In forensic pathology, the history includes scene and other investigative information, and the decedent's medical and social history. Such information is important for the correct certification of the cause and manner of death. Herein, the authors present a case originally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…We read with interest article by Prahlow S and Prahlow J. entitled "Homicide in a Horse Barn?" which describes a case of elderly female found partially nude, with injuries, on the floor of her horse barn (1). The autopsy shown that some of the injuries were determined to be postmortem, caused by horses.…”
Section: Sirmentioning
confidence: 99%
“…We read with interest article by Prahlow S and Prahlow J. entitled "Homicide in a Horse Barn?" which describes a case of elderly female found partially nude, with injuries, on the floor of her horse barn (1). The autopsy shown that some of the injuries were determined to be postmortem, caused by horses.…”
Section: Sirmentioning
confidence: 99%